Trichomoniasis and bacterial vaginosis in pregnancy: inadequately managed with the syndromic approach - M Romoren; M Velauthapillai; M Rahman; J Sundby; E Klouman; P Hjortdahl (The World Health Organization, 2007)
OBJECTIVE: To measure the prevalence of Trichomonas vaginalis (TV) infection and bacterial vaginosis (BV) among pregnant women in Botswana, and to evaluate the syndromic approach and alternative management strategies for these conditions in pregnancy. METHODS: In a cross-sectional study, 703 antenatal care attendees were interviewed and examined, and specimens were collected to identify TV, BV, Candida species, Chlamydia trachomatis and Neisseria gonorrhoeae. Information on reproductive tract infections earlier in pregnancy was obtained from a structured interview and the antenatal record. FINDINGS: TV was found in 19% and BV in 38% of the attendees. Three-fourths of women with TV or BV were asymptomatic. Syndromic management according to the vaginal discharge algorithm would lead to substantial under-diagnosis and over-treatment of TV and BV. Signs of vaginal discharge were more predictive of the presence of these conditions than were symptoms. Among the 546 attendees on a repeat antenatal visit, 142 (26%) had been diagnosed with vaginal discharge earlier in their pregnancy - 14 of them twice. In 143 cases, an attendee was diagnosed with vaginal discharge in the second or third trimester; however, metronidazole had been prescribed only 17 times (12%). CONCLUSION: Diagnosis and treatment of TV and BV among pregnant women in sub-Saharan Africa presents major challenges. Half the pregnant women in this study were diagnosed with TV or BV, but these conditions were not detected and treated during antenatal care with syndromic management. Also, health workers did not adhere to treatment guidelines. These results indicate that management guidelines for TV and BV in antenatal care should be revised.